Effectiveness of a Fishway for Restoring Passage of Colorado River Cutthroat Trout. (2nd November 2017) - Hodge, Brian W.; Fetherman, Eric R.; Rogers, Kevin B.; Henderson, Richard
Abstract: Little is known about the effectiveness of fishways for restoring passage to inland (nonanadromous) salmonids. We used PIT telemetry to evaluate the biological effectiveness of a vertical-slot fishway constructed to restore passage of adult Colorado River Cutthroat Trout Oncorhynchus clarkii pleuriticus (CRCT) in a small Rocky Mountain stream. Our objectives were to assess (1) fishway efficacy (whether or not the fishway restored fish passage), (2) approach efficiency (the probability that a tagged fish encountered the fishway; an index of population use), (3) attraction efficiency (the probability that a fish near the fishway located its entrance), and (4) passage efficiency (the probability that a fish entering the fishway navigated successfully through it). To account for antenna detection probabilities and avoid biases that can result from simple, proportion-based calculations, we used a variation of the Cormack–Jolly–Seber model to derive efficiency estimates. The fishway restored passage of adult CRCT to long-vacant habitats. Approach efficiency was 4%; attraction and passage efficiencies were 100%. We conclude that fishways can effectively restore passage of inland salmonids, and we recommend that additional fishway monitoring studies be conducted to inform decision-making and elucidate which designs and conditions will best facilitate passage. Received April 19, 2017; accepted September 26, 2017Published online November 6, 2017